ANALISIS OPTIMALISASI FUNGSI BALL JOINT PADA MESIN UJI TARIK DENGAN MENGGUNAKAN FEM - Herdiana, Ade (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
Provision of teaching aids for learning is a matter that is needed by academics, such as the tensile testing machine. Tensile testing machine consists of several components, including: Frame, power transfer screw, pulling throttle, fixed grip holder, cross head, pulling screw pair, power screw gear, drive gear, WPX gear box, chain, v-belt, driving pulley, electric motor, sprocket, WPA gearbox, drived pulley. With the tensile testing machine, academics know the characteristics of the material, as an important knowledge of material materials viewed from materials that have tensile strength, compressive strength, twisting force, shear force, modulus of elasticity, to where the material is already unable to withstand the load and break up (Fracture / Break). From the research results obtained a maximum load of 292 MPa far exceeds the yield stress of AISI 1035 material of 282.69 MPa, for Savety of Factor obtained 0.97 is also below the safety factor standard of 1.